Titelblad, kolofon, indholdsfortegnelse - Fjeldsøe, Michael; Holme Hansen, Thomas; Michelsen, Morten (Danish Yearbook of Musicology, 2000)
Editors: Michael Fjeldsøe, Thomas Holme Hansen, Morten Michelsen